Association between dietary sodium, potassium, and the sodium-to-potassium ratio and mortality: A 10-year analysis - Kwon, Yu-Jin; Lee, Hye Sun; Park, Goeun; Lee, Ji-Won (Frontiers in Nutrition, 2022)
There is inconclusive evidence of the association between dietary sodium, potassium, and the sodium-to-potassium ratio and all-cause and cardiovascular disease mortality. To investigate the association between dietary sodium, potassium, and the sodium-to-potassium ratio and all-cause and cardiovascular disease mortality risks. Data from 143,050 adult participants were analyzed from prospective 10-year community-based cohort analysis. Dietary sodium, potassium, and the sodium-to-potassium ratio at baseline were assessed by a food frequency questionnaire. In Cox proportional hazards regression models, the association between dietary sodium, potassium, and their ratio and all-cause and cardiovascular disease mortality was estimated using hazard ratios and 95% confidence intervals, and their predictive ability as mortality predictors was evaluated using Harrell’s c-index. During the mean (range) 10.1 (0.2–15.9) years of follow-up, 5436 participants died, of whom 985 died of cardiovascular causes. After adjustment for age, sex, body mass index, alcohol intake, smoking, regular exercise, total calorie intake, dyslipidemia, hypertension, diabetes, chronic kidney diseases, and potassium or sodium intake, respectively, sodium intake was unassociated with all-cause mortality whereas potassium intake was significantly associated inversely with all-cause (Quintile-5 vs. Quintile-1, hazard ratio, 95% confidence interval, 1.09, 0.97–1.22 and 0.79, 0.69–0.91, respectively). The sodium-to-potassium ratio was not significantly associated with all-cause mortality in the adjusted model, and similar trends were observed for cardiovascular disease mortality. Sodium intake and the sodium-to-potassium ratio were not significantly associated with all-cause and cardiovascular disease mortality. Potassium intake was significantly associated inversely with all-cause and cardiovascular disease mortality.